Topside Ionosphere Sounding From the CHAMP, GRACE, and GRACE‐FO Missions. Issue 3 (19th March 2023) - Schreiter, Lucas; Stolle, Claudia; Rauberg, Jan; Kervalishvili, Guram; van den Ijssel, Jose; Arnold, Daniel; Xiong, Chao; Callegare, Andyara
Abstract: Satellites in Low Earth Orbit (LEO) are essential for sounding the topside ionosphere. In this work, we present and validate a data set of Total Electron Content (TEC) and in situ electron density observations from the Gravity Recovery And Climate Experiment (GRACE) and GRACE‐Follow‐On missions as well as a TEC data set from the CHAllenging Minisatellite Payload mission. Concerning TEC, special emphasis is put to ensure optimal consistency to the already existing Swarm and Gravity field and steady‐state ocean circulation explorer (GOCE) TEC data sets. The newly processed satellite missions allow covering two full solar cycles with LEO slant TEC. Furthermore, the twin satellite missions GRACE and GRACE‐FO equipped with inter‐satellite K‐band ranging allows to derive the horizontal TEC and, due to the small inter‐satellite distance of the satellite pairs, an approximation for local electron density. However, the derived value of electron density is relative and requires calibration using external information. In this work, the calibration is performed using the IRI‐2016 model. Radar observations, as well as in situ electron density observations available from Swarm B Langmuir probes, are used for validation. Conjunctions between satellites are used to validate the TEC time series. The newly derived data set is shown to be highly consistent with the already existing data sets with standard deviations below 3 TECU for TEC (even 1 TECU was reached for low solar flux) and an offset below 7 × 10 10 m −3 with a standard deviation near 1 × 10 11 m −3 for the electron density. Key Points: Two full solar cycles are covered by Low Earth Orbit (LEO) Global Positioning System (GPS) Total Electron Content (TEC) observations by adding CHAllenging Minisatellite Payload (CHAMP), Gravity Recovery And Climate Experiment (GRACE) and GRACE‐Follow‐On (FO) to support Swarm Local electron density is approximated using inter‐satellite K‐band ranging of the GRACE satellites LEO GPS TEC from the missions considered and GRACE(‐FO) electron density observations are highly consistent to Swarm observations